3D liquid bioprinting of the PCL/β-TCP scaffolds - (:unkn) unknown (Trans Tech Publications Ltd, 2018)
In this present work, an original 3D bioprinting method has been developed by modifying an exceptional 3D printer. Using a composite material, bioprinting was carried out to create the ideal scaffold material to contribute regeneration of the certain amount of tissue types in humans. After bypassing the extruder and heating system of the 3D printer, instead of using solid filaments, polymer-ceramic composite was dissolved using an organic agent and bioprinting was conducted. During the bioprinting, dissolving agent was evaporated quickly and solidification process was completed. Despite of the traditional 3D printing, which benefits from the glass transition temperature of the materials, regardless of the temperature, rapid prototyping technology has been merged with controlled flow rate of the composite solution and evaporation of the solvents were adjusted meticulously for proper solidification and layer by layer bioprinting of the scaffolds. © 2018 Trans Tech Publications, Switzerland.
Keywords: 3D bioprinting; Composites; Polycaprolactone; β-Tricalcium phosphate